On discontinuous differential equations - Luis Domini dos Santos, Iguer (Revista de Matemática da UFOP, 2019)
The paper studies and compare generalized solutions to discontinuous differential equations. This way, are studied and compared the Euler, Filippov, Hermes, Krasovskii, and Sentis generalized solutions to discontinuous differential equations. In particular, are studied relations between Euler and Hermes solutions. In addition, it is  proved that Hermes solutions satisfy some properties that are analogous to the properties satisfied by Euler solutions.